PERANCANGAN TATA KELOLA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) BERBASIS ITIL V3 & SERVICE DESK STANDART (STUDI KASUS : RSUD KOTA KEDIRI) - Anita Sari Wardani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
Minister of Health Regulation No. 82 of 2013 Chapter IV related to IT Governance recommends implementing IT governance for SIMRS. This study aims to design IT governance for SIMRS in The Kediri City Hospital. The design of IT governance is carried out after analyzing the gap of the current capability level with the target RSUD. The results of the IT governance design, 1 IT organizational structure, 11 IT processes, and 20 IT documents, were successfully created and approved by The Kediri City Hospital.